(untitled) (Comparative & International Education Series, 2022)
According to HESA (2020), international students account for one-fifth of the total student population in the UK, among whom, over one-third of non-EU international students were from China. Employability is one of the main drivers for this influx of students, yet we know relatively little about what makes returning students employable in the Chinese job market. This reflective paper is based on a recent survey conducted by the authors examining the perspectives of Chinese students, Chinese employers, and UK teachers on international student employability. The paper identifies three issues that seem to create problems for returning students: namely, a reverse language barrier, a reverse culture shock and a mismatch between careers support and the needs of the Chinese employment market. The authors suggest some ways that students can be better prepared for their transition back into the Chinese employment market.